Variation in the surface radiation budget over different land covers in a subtropical humid region: evidence from ground observations - Feng, Huihui; Wang, Shihan; Xiong, Jian; Zou, Bin; Wang, Wei (Frontiers in Ecology and Evolution, 2023)
The surface radiation was a crucial variable for understanding global climate and eco-environment change, which exhibited significant variations. In this study, we used in situ ground observations to estimate the variation of surface radiation budget over grassland and urban areas in a subtropical humid region. Our results revealed a positive radiation budget that varied over different land covers. Specifically, grassland exhibited higher shortwave radiation, while urban area was characterized by the higher longwave radiation. Notably, the surface radiation budget (Rn) was much greater in grassland (77.60 W2/m) than that in urban area (61.93 W2/m), which was mainly attributed to the difference of longwave radiation. Additionally, the atmospheric pressure exerted significant correlation with the radiations, while precipitation and relative humidity presented relatively weak correlations. Furthermore, the correlations with climate were stronger in grassland than that in urban areas, suggesting complex interactions with anthropogenic factors during the process of urbanization. Results of this study would help reveal the characteristics and corresponding mechanisms of surface radiation budgets, which would support the climatic adaptation and ecology management.